Apocrine carcinoma in situ with microinvasion – A case report - Ognenoska-Jankovska, Biljana; Qerimi, Adelina; Stojkoska, Elena; Basheska, Neli (Macedonian Association of Pathology, 2016)
Objective: Invasive apocrine carcinoma is a very rare type of breast malignancy, with an incidence of 0.5-4%, which presumably develops from apocrine precancerous lesions. We report a case of microinvasive apocrine carcinoma which was diagnosed by fine needle aspiration cytology (FNAC) and confirmed by histopathology. Material and Methods: A 45-year-old woman following a routine mammography that showed irregular spiculated mass measuring approximately 2.5cm in the upper outer quadrant of the left breast was referred to our Department for FNAC. The patient subsequently underwent left-sided quadrantectomy and axillary lymph node dissection, followed by postoperative adjuvant chemotherapy and radiotherapy. After 3 years of follow-up, no local recurrence or metastases were found. Results: FNAC yielded moderately cellular smears composed of loosely cohesive clusters of large, polygonal cells with abundant, basophilic and granular cytoplasm suggestive of malignant neoplasm with apocrine features. On gross examination of the quadrantectomy specimen, a grayish-white, solid growth with pushing borders measuring 2.5x1.7x1.5 cm was identified. Twenty-one lymph nodes measuring from 0.3 to 1.3 cm were dissected. Histologically atypical apocrine adenosis, low- and high-grade apocrine ductal carcinoma in situ (ADCIS) and 9 foci of microinvasive apocrine carcinoma (0.1-0.5mm) were found. Apocrine metaplasia was identified in the surrounding ducts. No nodal involvement was observed and the surgical margins were tumor free. Immunohistochemistry revealed that malignant cells (ADCIS and microinvasive carcinoma) were strongly positive for gross cystic disease fluid protein-15, Her2, and androgen receptor, and negative for estrogen and progesterone receptors. Ki67 proliferative index was approximately 15-20%, while 20-25% of the tumor cells were immunoreactive for p53. Conclusions: Here we report a case in which all of the stages involved in apocrine carcinoma progression were identified, from benign metaplasia to hyperplasia, atypia, ADCIS, to microinvasive cancer.
Keywords: breast; apocrine carcinoma; precursor; cytology; histology; immunohistochemistry